Pemberdayaan Masyarakat Melalui Diversifikasi Produk Olahan Rebusan Daun Kelor sebagai Terapi Herbal Pasien Diabetes Mellitus - Ismail Ismail; Simunati Simunati; Sukmawati Sukmawati; Mardiana Mustafa (Celebes Health Journal, 2026)
Diabetes mellitus is a chronic disease that requires sustainable management, including through a community-based non-pharmacological approach. This community service activity aims to improve community knowledge and behavior and examine the use of boiled moringa leaves in controlling blood sugar levels. The activity was carried out in Rantoni and Lajoro Hamlets, Pakeng Village, Lembang District, Pinrang Regency, from March to April 2026, involving 50 respondents. The methods used included lectures, questions and answers, and discussions combined with demonstrations of moringa leaf processing. The results showed an increase in participant knowledge and changes in behavior in regular consumption of moringa leaves. The analysis showed that moringa leaf consumption was significantly associated with blood sugar control and was a dominant factor in increasing the chances of glycemic control. Thus, community empowerment through the use of moringa leaves has the potential to be an effective promotive and preventive strategy in managing diabetes mellitus at the community level.